The Effect of Interactive Multimedia and Learning Styles on Students' Physics Creative Thinking Skills - Syahriani Yulianci; Nurjumiati Nurjumiati; Asriyadin asriyadin; Adi Apriadi Adiansha (Jurnal Penelitian Pendidikan IPA, 2021)
One of the innovations in physics learning needs to be done by using creative learning media, namely interactive multimedia. This is done so that physics learning becomes more effective and not monotonous towards the delivery of material by the teacher. In addition to media factors, factors from within students need to be studied to improve the quality of learning physics. This study aims to test the effectiveness of interactive multimedia on students' creative thinking skills in physics. In addition, this study aims to influence learning styles on creative thinking skills and to see the interaction between interactive multimedia and learning styles in influencing creative thinking skills. This research is included in the quasi-experimental research. The total sample consisted of 74 tenth grade students, who were divided into two groups, namely the experimental class and the control class. The sample was determined by purposive sampling. Data on creative thinking skills were tested using N-Gain, and learning styles were analyzed quantitatively. To see the effectiveness of the research variables, an Anava test was performed. The results showed that interactive multimedia had an effect on students 'creative thinking skills, while the learning styles and interactions of the two independent variables did not affect students' creative thinking skills